Molecular Diagnostics in Colorectal Cancer - Rustam Effendi YS; Imelda Rey (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Colorectal cancer (CRC) presents in one of three  patterns: sporadic colorectal cancer in those without a family history (65-85%); those with a family history (familial CRC)       10-25% of cases; inherited CRC accounting for less of 10% cases and presents as well-characterized cancer predisposition syndromes including Lynch syndrome (hereditary non-polyposis colorectal cancer/HNPCC) which comprises about 1-5% of all colorectal cancer, and multiple polyps CRC, which includes familial adenomatous polyposis (FAP,1%), rare CRC syndrome 0.1 %).  Many efforts have been made to discover the genetic and molecular features of CRC, and there is more evidence that these features determine the prognosis and response to  treatment. Colorectal cancer (CRC) is a heterogeneous disease, with three known major molecular groups. The most common is the chromosomal instability group, characterized by an accumulation of mutations  in specific oncogens and tumor suppressor genes. The second is the microsatellite instability group, caused by the dysfunction of deoxyribonucleic acid (DNA) mismatch repair genes leading to genetic hypermutability. The CpG island methylation phenotype  (CIMP) is the third group, distinguished by hypermethylation. In this review we would like to provide an up-to-date overview of molecular  genetic aspects of CRC that are currently important and should guide clinical practice in colorectal cancer in the diagnosis and selection of therapy.